2016
DOI: 10.1002/dys.1528
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reports of Increased Prospective and Retrospective Memory Problems in Adults with Developmental Dyslexia

Abstract: Short-term and working memory problems in dyslexia are well-documented, but other memory domains have received little empirical scrutiny, despite some evidence to suggest that they might be impaired. Prospective memory is memory for delayed intentions, whilst retrospective memory relates to memory for personally experienced past events. To gain an understanding of subjective everyday memory experience, a self-report measure designed to tap prospective and retrospective memory was administered to 28 adults with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 79 publications
6
26
0
Order By: Relevance
“…These arguments provided the rationale for a recent program of research into PM in adults with dyslexia. Full details of the background characteristics of the samples tested are reported in Smith-Spark, Zięcik, and Sterling (2016a, 2016b, 2017a, 2017b.…”
Section: Focus Of the Review: Pm In Adultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These arguments provided the rationale for a recent program of research into PM in adults with dyslexia. Full details of the background characteristics of the samples tested are reported in Smith-Spark, Zięcik, and Sterling (2016a, 2016b, 2017a, 2017b.…”
Section: Focus Of the Review: Pm In Adultsmentioning
confidence: 99%
“…Whilst the effects of dyslexia on PM have only been explored directly very recently (Khan, 2014;Smith-Spark, Zięcik et al, 2016a, 2016b, 2017a, 2017b, earlier research has identified dyslexia-related difficulties in areas of cognition which could be argued to draw on similar cognitive abilities to those involved in PM. Problems in the areas of organization, time-keeping, and planning have been reported in dyslexia and the relevance of these abilities to PM has recently been highlighted by Waldum and McDaniel (2016) in relation to performing complex everyday PM tasks.…”
Section: Early Indirect Evidence Suggestive Of Pm Problemsmentioning
confidence: 99%
See 3 more Smart Citations